Anisotropic rotational diffusion and transient nonlinear responses of rigid polar macromolecules in a strong external electric field - COFFEY, WILLIAM THOMAS; KALYMYKOV, YURI PETROVICH (American Institute of Physics, 2007)
Nonlinear transient responses of polar polarizable particles (macromolecules) diluted in a nonpolar solvent to a sudden change in magnitude of a strong external dc field are evaluated using the anisotropic noninertial rotational diffusion model. The relaxation functions and relaxation times appropriate to the transient dynamic Kerr effect and nonlinear dielectric relaxation are calculated by solving the infinite hierarchy of differential-recurrence equations for statistical moments (ensemble averages of the Wigner D functions). The calculations involve matrix continued fractions, which ultimately yield the exact solution of the infinite hierarchy of differential-recurrence relations for the first- and second-order transient responses.
PUBLISHED
Keywords: Electronic & Electrical Engineering